Engineering nanostructural routes for enhancing thermoelectric performance: bulk to nanoscale - Mohanraman, Rajeshkumar; Lan, Tian-Wey; Hsiung, Te-Chih; Amada, Dedi; Lee, Ping-Chung; Ou, Min-Nan; Chen, Yang-Yuan (Frontiers in Chemistry, 2015)
Thermoelectricity is a very important physical property, especially its significance in heat-electricity conversion. If thermoelectric devices can be effectively applied to the recovery of the renewable energies, such as waste heat and solar energy, the energy shortage and global warming issues may be greatly relieved. This review focusses recent developments on the thermoelectric performance of a low-dimensional material, bulk nanostructured materials, conventional bulk materials etc. Particular emphasis is given on, how the nanostructure in nanostructured composites, confinement effects in one-dimensional nanowires and doping effects in conventional bulk composites plays an important role in ZT enhancement.